2018
DOI: 10.1002/hbm.24378
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive loading via mental arithmetic modulates effects of blink‐related oscillations on precuneus and ventral attention network regions

Abstract: Blink‐related oscillations (BROs) have been linked with environmental monitoring processes associated with blinking, with cortical activations in the bilateral precuneus. Although BROs have been described under resting and passive fixation conditions, little is known about their characteristics under cognitive loading. To address this, we investigated BRO effects during both mental arithmetic (MA) and passive fixation (PF) tasks using magnetoencephalography (n =20), while maintaining the same sensory environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 88 publications
6
18
0
Order By: Relevance
“…This clearly indicates that the cognitive load was not particularly increased during normal vocalization. After this important step, we did not find a significant difference in blink rate between the easy and difficult task, but there is a tendency towards a higher blink rate during difficult tasks, which has been reported previously [5,23,33]. Our results further showed that an increase above baseline and a clearly visible modulation due to task difficulty was only observed when the task was performed with vocalization.…”
Section: Plos Onesupporting
confidence: 81%
See 3 more Smart Citations
“…This clearly indicates that the cognitive load was not particularly increased during normal vocalization. After this important step, we did not find a significant difference in blink rate between the easy and difficult task, but there is a tendency towards a higher blink rate during difficult tasks, which has been reported previously [5,23,33]. Our results further showed that an increase above baseline and a clearly visible modulation due to task difficulty was only observed when the task was performed with vocalization.…”
Section: Plos Onesupporting
confidence: 81%
“…mental arithmetic, revealed contradictory outcomes. While some researchers showed a negative correlation between blink rate and cognitive load during mental arithmetic [24,25], other studies found an increase in blink rate for difficult arithmetic compared to rest or easy arithmetic [5,23]. The advantage of an arithmetic task, in comparison to our task, namely talking about a given topic, is that one can receive feedback as to the solution for such a task and easily control for the task fulfilment.…”
Section: Plos Onementioning
confidence: 80%
See 2 more Smart Citations
“…Artifact rejection was done using gradients (maximal allowed voltage step: 10 uV/ms and maximal allowed difference of values in intervals: 100 uV), and visually reviewed for each subject. In line with prior work (Liu et al, 2017, 2018), independent component analysis (ICA) was performed for artifact correction (e.g., blinks, saccades, cardiac activity, muscle contractions, breathing) using the Infomax algorithm (Lee et al, 1999). Segments were baseline corrected (−100 to 0 ms), low-passed filtered at 20 Hz, and averaged based on experimental condition (Luck, 2014).…”
Section: Methodsmentioning
confidence: 99%